Profile of publications about functional foods in Brazilian journals: a scientometric analysis from 2000 to 2015 and an overview of Brazilian legislation - Silva, Carlos Eduardo De Farias; Andrade, Nayana Pereira; Cerqueira, Raphaella Barbosa de Oliveira; Silva, Izabelle Caroline Caetano da; Cavalcante, Paula Acioly Wanderley; Abud, Ana Karla de Souza; Souza, José Edmundo Accioly de (Acta Scientiarum. Biological Sciences, 2017)
Functional foods have been highlighted by having, in addition to nutritional characteristics, the possibility of preventing risk and/or delaying the development of several non-communicable diseases (NCDs). In the last decade, many articles related to functional food have been published worldwide, and there is a need to understand how the theme is reflected in national journals. The present research aimed to collect information about publications covering the topic of functional foods in journals, synthesizing these data and interpreting them, evaluating the profile of the authors and a frequency of the articles involved with the subject by scientific journal and by State/region. Subsequently, they were evaluated as the most studied foods and as more used methodologies, besides a small discussion about the advances of the Brazilian legislation on the subject. Between 2000 and 2015, 118 articles were selected in 62 educational institutions from 18 Brazilian states. The South (44%) and Southeast (34%) regions were the ones that published more, having Rio Grande do Sul the largest representation (24%). The journal with the largest publication was Food and Nutrition and the authors’ academic formation was diverse (29 areas in total), in particular Food Technology (21%), Nutrition (18%) and Food Engineering (13%). The Brazilian legislation is in development and has a good perspective to include new foods/ingredients with functional property.